A exploração do açaí como alternativa para o desenvolvimento econômico da Amazônia Legal: estudo de caso do estado do Pará (1990- 2010) - Coutinho, Rebeca Venancio (2017)
Açaí (Euterpe oleracea) is a palm tree from the Amazon region that produces a purple colored fruit, widely used in making pulp, and is traditional in the food of much of northern Brazil. With the growth of demand in the late 1990s, interest in the management of açaí trees became attractive and, consequently, created market for the fruit and the pulp of the same. With the increase of açaí planting, pulp production became popular both in the national and international scenario, mainly due to its energy and nutritional value. This growth caused a wave of industrial establishment, whose objective was to serve the domestic and foreign markets of the state of Pará, since, internally; production became expressive in response to the demands from the 1990s. Considering these facts, this work was structured in three distinct chapters: in the first, the focus was directed to the commercial potentials of the açaí tree. In the second, to the concept of development, especially the regional and economic development. Finally, in the third chapter, we analyzed aspects such as production and national and international markets of açaí pulp produced in Pará from 1990 to 2010. It was found that the production of açaí aroused great interest due to its potentials and properties and became an important source of income and employment, which led to the conquest of new markets, which are of fundamental importance for the local economy. It was also noticed that the açaí is one of the products of the North region that had evolution in the supply, with the strong demand, in the national and international market and that açaí batters are important players in the productive chain In this research. We used the historical method, indirect documentation method and the case study method due to the bibliographical and documentary content of the same, which made possible its historical, theoretical and scientific foundation.